The Night Stalkers : top secret missions of the U.S. Army's Special Operations Aviation Regiment - Durant, Michael J., 1961-; Hartov, Steven; Johnson, Robert L., Lt. Col. (New York : New American Library, 2008)
Shares anecdotes from the army's elite aviation unit, describing the harrowing adventures of some of the world's top professional helicopter crews during their missions in Iran, Grenada, Iraq, and other locations.
Urgent fury -- Sign will -- Inbound hot -- Unarmed and scared shitless -- From the jaws of death -- Mogadishu -- A cold and distant peak -- The ghost of heroes.
Includes index.
"NAL Caliber."
Previously published in a G.P. Putnam's Sons edition in 2006.
Keywords: United States. -- Army. -- Special Operations Aviation Regiment, 160th -- History; Military helicopters -- United States; Special operations (Military science) -- United States -- History; History